Production Performance of Reciprocal Cross between IPB D2 and IPB D3 Chickens from 1 to 12 Weeks of Age Reared in the Tropics (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
At present, several local chicken breeds in Indonesia exhibit suboptimal production performance despitetheir goood adaptability to tropical conditions. A reciprocal cross between IPB D2 chickens and IPB D3chickens was carried out, resulting in IPB D2D3 and IPB D3D2 chickens. This study aimed to observe theeffects of crossbreeding on the production performance of these crossbred chickens in tropical regions.A total number of 27 IPB D2D3 and 48 IPB D3D2 crossbred chickens was used. All data were presentedby descriptive statistics (mean, SD, CV) and analyzed by inferential statistics (two-sample t-test andMann-Whitney U test) to determine differences between two types of crossbreds. The two-sample t-testwas applied for body weight and body weight gain of chickens aged 5 to 12 weeks. Meanwhile, thenonparametric Mann-Whitney U test was used for feed intake and body weight gain in chickens aged1 to 4 weeks. The results showed that at 12 weeks, the body weight of IPB D2D3 reached 1104.22 g formales and 975.55 g for females, while the body weight of IPB D3D2 reached 1090.39 g for males and959.64 g for females. Better feed intake and feed conversion were achieved by IPB D2D3 males and IPBD3D2 females.